New Nick Carter weekly; No. 28. July 10, 1897; Nick Carter at the track; or, How he became a dead game sport. - Carter, Nicholas (House name) (Salt Lake City, UT : Project Gutenberg, 2022)
"New Nick Carter Weekly; No. 28. July 10, 1897; Nick Carter at the Track" is a fictional detective narrative from the late 19th century. The story features the celebrated detective Nick Carter as he navigates the world of horse racing and gambling to confront a conspiracy aimed at sabotaging a prized racehorse named Denver Bay, which has significant stakes involved for local investors. At the start of the narrative, Nick Carter is approached by a distressed Wall Street broker, James Wheeler, who risks the money of two minor heirs in an attempt to recover losses from a previous theft. This leads Carter to uncover a nefarious plan involving the horse race, where rumors suggest that Denver Bay may be tampered with to ensure his loss. Carter takes on the case, revealing his capability for disguise and subterfuge as he immerses himself into the world of gambling and racing, embarking on a high-stakes investigation filled with deception, threats, and a race against time to save both the horse and his client$1 (Bs reputation before the race begins. (This is an automatically generated summary.)s
Release date is 2022-10-07
David Edwards and the Online Distributed Proofreading Team at https://www.pgdp.net (Northern Illinois University Digital Library)
Keywords: Dime novels -- Periodicals; Detective and mystery stories, American -- Periodicals